PENGARUH PENGGUNAAN MEDIA PAPAN KOTAK DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI SATUAN PANJANG - Wijayanti, Arini; Firdaus, Andi Mulawakkan (Almeera Education, 2023)
The problem in this research is whether the checkerboard media affects improving mathematics learning outcomes in long unit material for class III UPTD students at SDN 104 Inpres Makkaraeng. This type of research is experimental research. The population in this study were all class III students at UPTD SDN 104 Inpres Makkaraeng. Meanwhile, the researcher used a random sample for sampling, namely class III a with 23 students as the control class and class III b as the experimental class. The data collection techniques used by researchers are 1) Observation, 2) Pre-test and post-test given to students to determine student learning outcomes, and whether the results have improved or not. The results of the study are: In the control class, it can be seen that student learning outcomes have improved. The pretest result of the control class (III a) students was that students got an average score of 48.91. In the posted results of control class students (Class III a), the average data was 73.91 and was included in the category of incomplete KKM. The pretest result of experimental class students (III b) is that students get an average score of 53.21. As for the posted results of control class students (Class III b), the average data was 85.86. So the checkerboard media had an effect in improving the results learn mathematics in length unit material. The hypothesis put forward, namely, that the checkerboard media affects improving mathematics learning outcomes in long unit material for class III UPTD SDN 104 Inpres Makkaraeng, has been proven to be true.